Prescription Drug Abuse: A Comparison of Prescriber and Pharmacist Perspectives. (6th June 2013) - Hagemeier, Nicholas E.; Gray, Jeffrey A.; Pack, Robert P.
<x xml:space="preserve">Abstract</x> This study compared perceptions of prescribers and pharmacists (N = 89) regarding multiple aspects of prescription drug abuse. Questionnaires were developed to assess perceptions regarding the prevalence of prescription drug abuse, self-perceived communication competence, and additional communication and prescription drug abuse domains. Pharmacists perceived a larger percentage of patients (41%) to be abusing opioid pain relievers as compared with their prescriber colleagues (17%). Both prescribers and pharmacists indicated improvements in prescriber–pharmacist communication would serve to deter prescription drug abuse. Self-efficacy beliefs for detecting and discussing prescription drug abuse with patients were low for both cohorts. Implications and limitations are noted. Year of data collection: 2012 Setting: Rural Appalachia Data Collection Instruments: Prescriber- and pharmacist-specific survey instruments Data Analysis Techniques: Independent samples t-test; Mann-Whitney U test